A Word of Caution for Future Studies in Patellofemoral Pain: A Systematic Review With Meta-analysis. Issue 2 (February 2021) - Grant, Camila; Fick, Cameron N.; Welsh, Judith; McConnell, Jenny; Sheehan, Frances T.
Background: Patellar maltracking is widely accepted as an underlying mechanism of patellofemoral pain. However, methodological differences in the literature hinder our ability to generate a universal quantitative definition of pathological patellofemoral kinematics (patellar maltracking) in patellofemoral pain, leaving us unable to determine the cause of patellofemoral pain. Purpose: To systematically review the literature to provide evidence regarding the influence of confounding variables on patellofemoral kinematics. Study Design: Systematic review and random effects meta-analysis of control-case studies. Methods: A literature search of case-control studies that evaluated patellofemoral kinematics at or near full extension and were written in English was conducted using Embase, PubMed, Scopus, and Web of Science up to September 2019. Cases were defined as patients with patellofemoral pain. Studies were eliminated if they lacked quantitative findings; had a primary aim to assess therapy efficacy; or included participants with osteoarthritis and/or previous trauma, pathology, or surgery. A quality assessment checklist was employed to evaluate each study. Meta-analyses were conducted to determine the influence of confounding variables on measures of patellofemoral kinematics. Results: Forty studies met the selection criteria, with quality scores ranging from 13% to 81%. Patient characteristics, data acquisition, and measurement methods were the primary sources of methodological variability. Active quadriceps significantly increased lateral shift (standardized mean difference [SMD]shift = 0.33; P = .0102) and lateral tilt (SMDtilt = 0.43; P = .006) maltracking. Individuals with pain secondary to dislocation had greater effect sizes for lateral maltracking than had those with isolated patellofemoral pain (ΔSMDshift = 0.71, P = .0071; ΔSMDtilt = 1.38, P = .0055). Conclusion: This review exposed large methodological variability across the literature, which not only hinders the generalization of results, but ultimately mitigates our understanding of the underlying mechanism of patellofemoral pain. Although our meta-analyses support the diagnostic value of maltracking in patellofemoral pain, the numerous distinct methods for measuring maltracking and the limited control for cofounding variables across the literature prohibit defining a single quantitative profile. Compliance with specific standards for anatomic and outcome measures must be addressed by the scientific and clinical community to establish methodological uniformity in this field.